Pengembangan Paket Miniatur Sistem Tata Surya Dalam Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Untuk Meningkatkan Hasil Belajar Kognitif IPA Siswa Kelas VI SD - Marya Dalena; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
The aim of this research is to develop, describe the level of feasibility, determine user responses and determine the effectiveness of developing a Miniature Solar System Package in Numbered Head Together (NHT) Cooperative Learning to Improve Science Cognitive Learning Outcomes for Class VI Elementary School Students. The type of research used is research and development. The research model in developing teaching materials is the ADDIE model. The type of data used is quantitative and qualitative data using instruments in the form of Pre-research Phase Interview Sheets, Media Expert Validation Instruments, materials and language, Student Response Questionnaire Instruments, Observation Guide Sheets, Question Validation Instruments, test sheets. Based on the research results, it can be concluded that the teaching materials that have been developed are suitable for use as teaching materials in class IV Indonesian language content. The expert validation results were 0.824 from material expert validation, 0.88 from design validation, and 0.874 from language expert validation. The response from students obtained a percentage of 94.5% with very good criteria. The teaching materials developed are effective in improving the learning outcomes of class IV students at SDIT UMMI Elementary School, Bengkulu City.